Dogmatic Criticism towards the Need of Religion: An Islamic Response (Al-Qamar, 2023)
This analytical study delves into the subject of dogmatic criticism concerning the necessity of religion, focusing specifically on Islam's response. It aims to explore the various dimensions of dogmatic criticism and its impact on religious belief systems, particularly within the context of Islam. The study also seeks to examine Islam's multifaceted responses to these critiques. By analyzing the interplay between dogmatic criticism and Islam's response, this study aims to shed light on the complexities surrounding the need for religion in contemporary society.
Keywords: Dogmatic Criticism; Need of Religion; Islamic Response